The characteristic features of the syntax of modern Turkish language. - Andabayeva., D. A.; Avakova, R. A.; Kortabayeva, G. K. (Journal of Oriental Studies, 2016)
This article is devoted to the peculiarities of Turkish syntax , basic syntactic units and the nature of the interaction of elements within the linguistic system. Classification of methods is given by the example of syntactic relations of Turkish language and specificity of combining the components . Briefly examines the history of the study of the question of theoretical syntax in general and in particular the Turkic syntax.Describes the syntactic units and differentiated concept of word and phrase.